(untitled) (Latakia University Journal -Biological Sciences Series, 2023)
Suitability of chicken intestine as an alternate protein source was evaluated for the diet of common carp (Cyprinus carpio L.) fingerlings farmed in external cement ponds. Two experimental diets were formulated from row chicken intestine (T1) and boiled chicken intestine (T2). Fingerlings were brought from General Authority for Fish Resources and Aquatic with average initial weight (43.66±0.47)g for (T1) and for (38.83±0.84)g for (T2) . Fingerlings were fed twice a day for five months. Percentage of protein, fat, ash and moisture for the experimental diets were analyzed. Best production indicators were recorded in (T2) with daily growth rate (2.86±0.15) and protein content in fish meat (17.84±0.03) than (T1) which recorded (2.56±0.15) and (17.67±0.06) respectively. Food conversion ratios were close with preference to (T2). Food conversion ratio recorded (2.07±0.07) in (T2) compared to (2.23±0.09) in (T1). The results of the present study concluded that it is possible to use boiled chicken intestine as a single component in common carp diets with good production and health indicators.